Investigating Strategies to Enhance the Aqueous Solubility of Ketamine HCl for Intranasal Delivery - Sourour Idoudi; Alaaeldin Saleh; Mohammed Akkbik; Leena Amine; Khalid Alansari; Ousama Rachid; Alaaldin M. Alkilany (Pharmaceutics)
Background: Ketamine HCl, an FDA-approved therapeutic, is administered through various routes, including intranasal delivery. Administering an adequate therapeutic dose of intranasal ketamine HCl is challenging due to the limited volume that can be delivered intranasally given the current commercially available concentrations. Objectives: This study investigates solubilizing strategies to enhance the aqueous solubility of ketamine HCl for intranasal administration. Methods: We assessed the solubility profile of ketamine HCl by evaluating factors such as pH, co-solvents, and surfactants. Additionally, we developed and validated a UV-Vis spectroscopy method for ketamine HCl analysis. Results: Our solubility screening in various organic co-solvents revealed the following order of effectiveness in enhancing solubility: methanol > water > propylene glycol > ethanol > dimethyl sulfoxide (DMSO) > N-methyl-2-pyrrolidone (NMP). Despite methanol’s superior solubility, its potential toxicity, coupled with the relatively lower effectiveness of other solvents compared to water, suggests that a co-solvency approach is not advantageous for ketamine HCl. We found that ketamine HCl solubility increased with medium acidity, with pH 3.5 being the optimal for further formulation studies. The impact of pharmaceutical surfactants on ketamine HCl solubility at an acidic pH was also evaluated. Surfactants tested included SDS, PEG 400, PVP, Tween 20, poloxamer 188, and lecithin. Notably, PEG 400 and PVP reduced solubility due to a salting-out effect, whereas Tween 80, lecithin, and poloxamer 188 slightly improved solubility through micelle formation. Among the surfactants tested, 1% SDS emerged as the most effective in enhancing ketamine HCl solubility. Conclusions: These outcomes highlight the potential of these solubilization strategies to address the solubility limitations of ketamine HCl, enabling the preparation of highly concentrated ketamine HCl formulations for intranasal delivery.